Incentivizing Investors for a Greener Economy - Nguyen, Nam; Rivera, Alejandro; Zhang, Harold H. (Journal of Financial and Quantitative Analysis, 2025)
Abstract We demonstrate that investment income taxes incentivize capital allocation to the ecofriendly green sector away from the non-ecofriendly brown sector in a stylized economy. This tax reduces the arrival intensity of climate disasters, delivers the socially optimal allocation, and can be jointly implemented with a carbon tax, expanding policymakers’ toolkit to reduce climate disasters. Extending the model with heterogeneous investors, we show that investment income taxes can obtain support from a political majority and thereby relax political constraints faced by a carbon tax alone.